Transformasi Digital Organisasi Pengelolaan Zakat : Indeks Kesiapan dan Ekosistem Zakat Pada Baznas Pamekasan - Imron, Moh; Fadil, Ahmad (Ulumuna: Jurnal Studi Keilsman, 2024)
Digital transformation of zakat management carried out by BAZNAS is an important aspect in maximizing the potential of zakat. In addition, in supporting the digitalization of zakat, it is necessary to have a zakat ecosystem at the central, provincial, and regional levels, especially BAZNAS Pamekasan Regency. The purpose of this study is to determine the digital zakat readiness index and zakat ecosystem as well as the obstacles faced by BAZNAS Pamekasan. This research is a descriptive qualitative research. Primary data sources are obtained from observations and interviews, secondary data comes from literature review. The results showed that the digital transformation measured on the OPZ readiness index of BAZNAS Pamekasan through the use of SIMBA, while in building the zakat ecosystem, BAZNAS Pamekasan has coordinated with various parties, especially the local government to maximize the zakat potential in Pamekasan district, even so there are still obstacles faced by BAZNAS in managing zakat due to the lack of public literacy and the lack of local government role in empowering BAZNAS Pamekasan,